Teori Belajar Dalam Psikologi Pendidikan - Akhmad Shohibul Ilman; Khaerul Dionprawitno (Yayasan Al-Afif, 2025)
This study aims to analyse various learning theories in the context of educational psychology and their implications for learning practices in academic settings. Learning theories are an important foundation for teachers and educators in understanding how learners acquire, process, and retain information. This study uses a qualitative approach with a literature review method that examines major theories such as behaviourism, cognitivism, constructivism, and humanism. The results of the study show that each theory has a significant contribution to modern educational practice. Behaviourism emphasises the importance of reinforcement and habituation; cognitivism focuses on internal mental processes; constructivism emphasises the active role of learners in constructing knowledge; while humanism focuses on the development of self-potential. The practical implication of this study is the importance of integrating various learning theories contextually to create adaptive and meaningful learning